An 18-Year-Old Male With X-linked Lymphoproliferative Syndrome Type 1 Who Developed Primary Central Nervous System Lymphoma 6 Months After Primary Epstein-Barr Virus Infection. Issue 8 (November 2019) - Kusano, Nobuyoshi; Sakata, Naoki; Sugimoto, Keisuke; Miyazawa, Tomoki; Ueda, Satoshi; Okano, Munehiro; Imadome, Ken-Ichi; Hoshino, Akihiro; Kanegane, Hirokazu; Kimura, Masatomo; Sato, Takao; Okada, Mitsuru; et al.
Abstract : X-linked lymphoproliferative syndrome type 1 (XLP1) is a rare congenital immunodeficiency disease. We report the case of an 18-year-old male who developed hemophagocytic lymphohistiocytosis (HLH) with neurologic complications after primary Epstein-Barr virus (EBV) infection and subsequently developed EBV-related central nervous system lymphoma (CNSL). Given the vulnerability to EBV, he was finally diagnosed with XLP1 and treated with whole-brain irradiation along with chemotherapy and subsequent allogeneic hematopoietic stem cell transplantation from a SH2D1A wild-type sibling donor. Although the prognosis for CNSL is generally dismal, reconstitution of the immune system from a normal donor contributed to the patient remaining in remission for 30 months.